A systematic meta‐analysis of immune signatures in patients with COVID‐19. (20th November 2020) - Liu, Kun; Yang, Tong; Peng, Xue‐Fang; Lv, Shou‐Ming; Ye, Xiao‐lei; Zhao, Tian‐Shuo; Li, Jia‐Chen; Shao, Zhong‐Jun; Lu, Qing‐Bin; Li, Jing‐Yun; Liu, Wei
Summary: Currently severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) transmission has been on the rise worldwide. Predicting outcome in COVID‐19 remains challenging, and the search for more robust predictors continues. We made a systematic meta‐analysis on the current literature from 1 January 2020 to 15 August 2020 that independently evaluated 32 circulatory immunological signatures that were compared between patients with different disease severity was made. Their roles as predictors of disease severity were determined as well. A total of 149 distinct studies that evaluated ten cytokines, four antibodies, four T cells, B cells, NK cells, neutrophils, monocytes, eosinophils and basophils were included. Compared with the non‐severe patients of COVID‐19, serum levels of Interleukins (IL)‐2, IL‐2R, IL‐4, IL‐6, IL‐8, IL‐10 and tumor necrosis factor α were significantly up‐regulated in severe patients, with the largest inter‐group differences observed for IL‐6 and IL‐10. In contrast, IL‐5, IL‐1β and Interferon (IFN)‐γ did not show significant inter‐group difference. Four mediators of T cells count, including CD3 + T, CD4 + T, CD8 + T, CD4 + CD25 + CD127 ‐ Treg, together with CD19 + B cells count and CD16 + CD56 + NK cells were all consistently and significantly depressed in severe group than in non‐severe group. SARS‐CoV‐2 specific IgA and IgG antibodies were significantly higher in severe group than in non‐severe group, while IgM antibody in the severe patients was slightly lower than those in the non‐severe patients, and IgE antibody showed no significant inter‐group differences. The combination of cytokines, especially IL‐6 and IL‐10, and T cell related immune signatures can be used as robust biomarkers to predict disease severity following SARS‐CoV‐2 infection.